Pre-neutron-emission mass distributions for reaction ^238U（n, f） up to 60 MeV - 孙小军 余呈刚 王宁 杨永栩 潘成华 (中国物理C：英文版, 2015)
Abstract： The pre-neutron-emission mass distributions for reaction ^238U（n, f） up to 60 MeV are systematically studied with an empirical fission potential model. The energy dependence of the peaks and valleys of the pre-neutronemission mass distributions is described by an exponential form based on the newly measured data. The energy dependence of evaporation neutrons before scission is also considered, which plays a crucial role in the reasonable description of the mass distributions. The measured ^238U（n, f） are reasonably well reproduced up to 60 predicted using this approach. data of the pre-neutron-emission mass distributions for reaction MeV. The mass distributions at unmeasured energies are also